2011
DOI: 10.3113/fai.2011.0933
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results Following Keller Resection Arthroplasty for Hallux Rigidus

Abstract: Background: We assessed the long-term results following Keller resection arthroplasty for the treatment of hallux rigidus. We then compared them with alternative surgical methods like cheilectomy, arthrodesis and joint replacement. Methods: Eighty-seven cases of Keller resection arthroplasty for hallux rigidus were reviewed with mean followup of 23 years. Their mean age at time of surgery was 50 years. Analysis included personal clinical evaluation with the AOFAS Hallux Score, quality-of-life assessment using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Only 3 studies reported AOFAS-HMI scores ranging between 83 and 89 points with a wide spread in follow-up from 14 months to 23 years. 15,34,43,44 Our results are consistent with these studies, which showed that the good midterm results of a Keller’s arthroplasty remain stable over a long time. In addition, the fear of having a nonfunctional first ray resulting in limitations and/or pain was not proved with these results.…”
Section: Discussionsupporting
confidence: 90%
“…Only 3 studies reported AOFAS-HMI scores ranging between 83 and 89 points with a wide spread in follow-up from 14 months to 23 years. 15,34,43,44 Our results are consistent with these studies, which showed that the good midterm results of a Keller’s arthroplasty remain stable over a long time. In addition, the fear of having a nonfunctional first ray resulting in limitations and/or pain was not proved with these results.…”
Section: Discussionsupporting
confidence: 90%
“…In four of those cases two K-wires were used, in one case we used memory staple and in ten cases two Barouk screws to fix the arthrodesis. In three cases we performed resection of the MTP joint [24,25] (Keller’s procedure) when patients with considerably restricted physical activity refused the arthrodesis of the first MTP joint. In one case the Akin procedure [26] of the great toe was done.…”
Section: Resultsmentioning
confidence: 99%
“…Schneider et al retrospectively reviewed 87 cases after Keller resection arthroplasty at average follow-up of 23 years and found a mean American Orthopedic Foot and Ankle Society (AOFAS) score of 83. 21 While 94% of patients would have their surgery again and the revision rate was 5%, due to the advancement in other treatments, this procedure is rarely performed.…”
Section: Operative Managementmentioning
confidence: 99%